Development of a high resolution voxelised head phantom for medical physics applications. (January 2017) - Giacometti, V.; Guatelli, S.; Bazalova-Carter, M.; Rosenfeld, A.B.; Schulte, R.W.
Highlights: Development of a novel voxelised head phantom with high (sub-mm) resolution. The phantom is an accurate representation of an existing physical head phantom. The phantom was modelled in Geant4 to characterize a novel proton CT (pCT) system. The study shows the advantages of adopting a high resolution digital phantom in pCT. The digital phantom can be adopted in dosimetric and imaging studies. Abstract: Computational anthropomorphic phantoms have become an important investigation tool for medical imaging and dosimetry for radiotherapy and radiation protection. The development of computational phantoms with realistic anatomical features contribute significantly to the development of novel methods in medical physics. For many applications, it is desirable that such computational phantoms have a real-world physical counterpart in order to verify the obtained results. In this work, we report the development of a voxelised phantom, the HIGH_RES_HEAD, modelling a paediatric head based on the commercial phantom 715-HN (CIRS). HIGH_RES_HEAD is unique for its anatomical details and high spatial resolution (0.18 × 0.18 mm 2 pixel size). The development of such a phantom was required to investigate the performance of a new proton computed tomography (pCT) system, in terms of detector technology and image reconstruction algorithms. The HIGH_RES_HEAD was used in an ad-hoc Geant4 simulation modelling the pCT system. The simulation application was previously validated with respect to experimental results. When compared to a standard spatial resolution voxelised phantom of the same paediatric head, it was shown that in pCT reconstruction studies, the use of the HIGH_RES_HEAD translates into a reduction from 2% to 0.7% of the average relative stopping power difference between experimental and simulated results thus improving the overall quality of the head phantom simulation. The HIGH_RES_HEAD can also be used for other medical physics applications such as treatment planning studies. A second version of the voxelised phantom was created that contains a prototypic base of skull tumour and surrounding organs at risk.